The role of plasma exchange for fulminant lupus with multiorgan involvement - Mathew, Meghena; Sairam, Srilekha; Ramakrishnan, Nagarajan; K Mani, Ashwin (Indian Journal of Case Reports, 2020)
Fulminant lupus is a fatal presentation of systemic lupus erythematosus (SLE) and immunosuppression is the key treatment modality. However, there can be conditions that preclude their use. We present the case report of a 21-years-old female with SLE with multiorgan involvement where plasma exchange resulted in good recovery of all the affected vital organs. She presented with fever and generalized lymphadenopathy and then developed cardiac, pulmonary, and neurologic involvement of lupus. She was started on plasma exchange. Her blood culture grew Streptococcus pneumoniae. While on plasma exchange, she was found to have bilateral ptosis. Acetylcholine receptor antibody was positive confirming Myasthenia gravis. She showed good recovery of all organs following plasma exchange. This case report highlights the positive role of plasma exchange in a patient with fulminant lupus and concomitant sepsis. We see that this is the second such case reported where plasma exchange had a positive outcome.